(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
In this study, Physico-chemical and biological analysis of river Ngadda and pond water collected in Ramat Polytechnic ware evaluated to compare their compliance with World Health Organisation (WHO) using standard analytical methods. The parameters evaluated include: K, Mg, Mn, NO3, Iron, PO4, and hardness pH, Cl, K, Ca, EC, OD, BOD, TDS, Mg, Mn, NO3, PO4, Iron and coliform counts. The results from the laboratory analysis showed some of the physico-chemical parameters conform with WHO except K, Mg, Mn, NO3, Iron, PO4, and hardness that were found to be above the WHO standard. Coliform count was found to be present in the water that exceed the WHO standard. The t-test result reveals that there is no significant difference between the river and pond water properties with the WHO standard. The results of this study indicate that model water treatment plant could be suitable for treating water for domestic purposes.